Drug Cost-Effectiveness Assessments Require Standards for Rigor and Inclusion - Tia Goss Sawhney; Neil Thakur (Journal of Health Economics and Outcomes Research)
The Institute for Clinical and Economic Review (ICER), a nonprofit, nongovernmental organization, is the predominant independent price assessor in the United States. ICER’s cost effectiveness assessments are increasingly being used to support health insurance coverage and healthcare policy decisions. ICER often does not apply rigorous data quality and inclusion criteria to either the assumptions embedded within their cost-effectiveness models or the data inputted into the models. Poor quality assumptions and data can lead to poor quality assessments.